Shifting Gears : Digitization and Services-Led Development - World Bank (Washington, DC: World Bank, 2021)
South Asia region’s economies continue on a recovery path, with production and export having recovered to pre-COVID trend levels. But the recovery has been uneven across countries and sectors, and significant risks exist that could jeopardize short-term recovery and long-term growth. Over the short-term, low vaccination rates in most countries in the region make the population and economies vulnerable to future COVID waves and lockdowns; supply shortages due to global supply bottlenecks continue to put upward pressure on (food) inflation, especially after consumption recovers. Over the long-term, the region faces long-lasting scarring effects from the pandemic. The emergence of a new services economy creates an opportunity for the region to shift gears and to move towards a services-led development model. The importance of services has been increasing over time and got a further boost during the response to the COVID pandemic, when digital technologies became critical. This new services economy comprises not just the ICT sector, but also business and professional services that are increasingly critical inputs into manufacturing and other sectors, and digital platforms that are creating new markets. It can become the driver of development in South Asia because 1) Services are increasingly tradable and also represent a large part of value added incorporated in the exports of goods. 2) Services firms can drive productivity growth because of innovations that make their own products and other industries more efficient 3) The services sector also generates jobs and helps upgrading skills through on-the-job training. To unleash the potential of the new services economy, policy makers should rethink regulations and establish new institutions to enable 1) competition and innovation 2) increased labor mobility and up-skilling, through education and on-the job training; 3) the absorption of new services by firms and households. Governments in South Asia are addressing these new realities, but they face major challenges. With countries worldwide struggling to find an optimal institutional environment for the new services sectors, a good option for South Asia is to experiment with regulatory sandboxes.